On the Detection of COVID‐Driven Changes in Atmospheric Carbon Dioxide. Issue 22 (19th November 2021) - Lovenduski, Nicole S.; Chatterjee, Abhishek; Swart, Neil C.; Fyfe, John C.; Keeling, Ralph F.; Schimel, David
Abstract: We assess the detectability of COVID‐like emissions reductions in global atmospheric CO2 concentrations using a suite of large ensembles conducted with an Earth system model. We find a unique fingerprint of COVID in the simulated growth rate of CO2 sampled at the locations of surface measurement sites. Negative anomalies in growth rates persist from January 2020 through December 2021, reaching a maximum in February 2021. However, this fingerprint is not formally detectable unless we force the model with unrealistically large emissions reductions (2 or 4 times the observed reductions). Internal variability and carbon‐concentration feedbacks obscure the detectability of short‐term emission reductions in atmospheric CO2 . COVID‐driven changes in the simulated, column‐averaged dry air mole fractions of CO2 are eclipsed by large internal variability. Carbon‐concentration feedbacks begin to operate almost immediately after the emissions reduction; these feedbacks reduce the emissions‐driven signal in the atmosphere carbon reservoir and further confound signal detection. Plain Language Summary: COVID pandemic lockdowns suddenly slowed the rate at which we burned fossil fuels and released carbon dioxide into the atmosphere, yet we cannot find any significant reductions in the growth of carbon dioxide in the atmosphere from our measurements. Here we provide some reasons to explain this conundrum. We use a climate model to mimic the changes in atmospheric carbon that would occur with different amounts of reductions in fossil fuel burning. We find that it is hard to see the change in fossil fuel burning in atmospheric carbon dioxide or its growth because of a large background component of natural variability. In addition, once we reduce our fossil fuel burning and the amount of carbon dioxide in the atmosphere decreases, the ocean and land also stop taking up as much carbon as normal. As we will soon lower our fossil fuel burning on purpose to slow climate change, our findings forewarn of the difficulties of detecting the effects of this in measurements of atmospheric carbon dioxide. Key Points: Climate model simulations suggest a lagged response in the global growth rate of atmospheric CO2 due to COVID‐19 emissions reductions Detection of this reduction in observations is hampered by internal variability combined with reduced ocean and land uptake of CO2 Our results foreshadow the challenges of detecting the effects of CO2 mitigation efforts to meet the Paris climate agreement